2020
DOI: 10.1111/jonm.12987
|View full text |Cite
|
Sign up to set email alerts
|

Predicting workplace loneliness in the nursing profession

Abstract: Aim:This study examined a model investigating how social interaction variables (leader-member exchange (interactions between managers and nurses), trust, and communication frequency) and work meaningfulness influence nurses' experiences of workplace loneliness. Background:As workplace loneliness can result in lower job satisfaction and a decrease in workers' health, understanding the contributing factors to loneliness at work is important. Method:In this cross-sectional study, Turkish nurses (N = 864) complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…It is more potent if the employee feels that the work is without meaning. (39,40). In our study, the CNPs pointed out that before, in the ambulance unit, there was always another person to share thoughts and decisions.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It is more potent if the employee feels that the work is without meaning. (39,40). In our study, the CNPs pointed out that before, in the ambulance unit, there was always another person to share thoughts and decisions.…”
Section: Discussionmentioning
confidence: 71%
“…Now the distances between the patients could be very long, and the visits can keep the CNP on the road all shift without seeing any other coworkers during the day. One rewarding and personally relevant and emotionally salient solution has been that the team-leaders meet the team members frequently (40) and actively share feedback keeping the members engaged in their integrated teams (41). However, paramedics have stated that they rarely received feedback from patient interactions (42).…”
Section: Discussionmentioning
confidence: 99%
“…Isolation and loneliness in the workplace lead to negative effects on work performance (16). A study conducted in a Turkish healthcare institution found that loneliness at work had a considerable effect on work alienation and increased workplace stress (17). This issue does not seem to be insulated to paramedics who transition to managers, as the nursing profession experience the same obstacle (18).…”
Section: Discussionmentioning
confidence: 99%
“…Steger and colleagues reported data confirming the scale’s validity and showed a high level of internal consistency with an alpha coefficient of 0.93 [ 15 ]. The instrument has been used in numerous previous studies of health-care employees [ 16 18 ]. Furthermore, we applied the 5-item Job Satisfaction Scale by Judge et al Internal consistency of this scale has been proven high with Cronbach’s alpha of 0.8 and higher [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%